Ablation versus medication as initial therapy for paroxysmal atrial fibrillation: An updated meta‐analysis of randomized controlled trials. Issue 6 (29th September 2021) - Kewcharoen, Jakrin; Prasitlumkum, Narut; Chokesuwattanaskul, Ronpichai; Yi, Ruiyang; Jongnarangsin, Krit; Bunch, Thomas J.; Ranjan, Ravi; Navaravong, Leenhapong
Abstract: Background: Recent randomized controlled trials (RCTs) suggest that ablation is superior to antiarrhythmic drugs (AADs) as an initial therapy for paroxysmal atrial fibrillation (pAF) to prevent arrhythmia recurrences. We performed an updated meta‐analysis of RCTs, to include recent data from cryoballoon‐based ablation and to compare arrhythmia‐free survival and adverse events between ablation and AADs. Methods: We searched MEDLINE and EMBASE from inception to December 2020. We included RCT comparing patients with pAF undergoing ablation or receiving AADs as an initial therapy. We combined data using the random‐effects model to calculate hazards ratio (HR) for arrhythmia‐free survival and odds ratio (OR) for adverse events. Results: Five studies from 2005 to 2020 involving 985 patients were included (495 patients and 490 patients underwent ablation and medication as initial therapy, respectively). Patients who underwent ablation had higher freedom from atrial tachyarrhythmias (ATs) during the 12‐24 months follow‐up period (pooled HR = 0.48, 95% CI: 0.40‐0.59, P  < .001). In a subgroup analysis of ablation method used, both cryoablation group (pooled HR = 0.49, 95% CI: 0.38‐0.64, P  < .001) and radiofrequency ablation group (pooled HR = 0.47, 95%CI: 0.35‐0.64, P  < .001) showed reduction in AT recurrence compared with AAD group. There were no differences in adverse events including cerebrovascular accident, pericardial effusion or tamponade, pulmonary vein stenosis, acute coronary syndrome, deep vein thrombosis and pulmonary embolism, and bradycardia requiring a pacemaker. Conclusion: Catheter ablation (both cryoablation and radiofrequency ablation) is superior to AAD as an initial therapy for pAF in efficacy for reducing AT recurrences without a compromise in adverse events. Abstract : We performed meta‐analysis of the most recent randomized control trials evaluating atrial fibrillation ablation as the first line therapy